2023
DOI: 10.1039/d3ta03079b
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the role of surface and interfacial defects in hydrogen production to construct an all-in-one broken-gap photocatalyst

Jingwei Li,
Xuyu Wang,
Hongli Fang
et al.

Abstract: A rational design of WO3−x/ZnFe2O4−x broken-gap heterojunction achieved higher charge carrier separation, light-harvesting ability, and good surface reaction, as an all-in-one photocatalyst for H2 generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Li et al [70] conducted a DFT-calculations-supported characterization experiment by locating the broken-gap heterojunction at the interface or surface. The results showed that the broken-gap heterojunction rich in defects had higher carrier separation and light collection ability and good surface reaction.…”
Section: Photocatalytic Hydrogen Productionmentioning
confidence: 99%
“…Li et al [70] conducted a DFT-calculations-supported characterization experiment by locating the broken-gap heterojunction at the interface or surface. The results showed that the broken-gap heterojunction rich in defects had higher carrier separation and light collection ability and good surface reaction.…”
Section: Photocatalytic Hydrogen Productionmentioning
confidence: 99%